The Tuma Underworld of Love. Erotic and other narrative songs of the Trobriand Islanders and their spirits of the dead - Gunter Senft (Culture and Language Use, 2011)
The Trobriand Islanders' eschatological belief system explains what happens when someone dies. Bronislaw Malinowski described essentials of this eschatology in his articles "Baloma: the Spirits of the Dead in the Trobriand Islands" and "Myth in Primitive Psychology". There he also presented the Trobrianders' belief that a "baloma" can be reborn; he claimed that Trobrianders are unaware of the father's role as genitor. This volume presents a critical review of Malinowski's ethnography of Trobriand eschatology - finally settling the "virgin birth" controversy. It also documents the ritualized and highly poetic "wosi milamala" - the harvest festival songs. They are sung in an archaic variety of Kilivila called "biga baloma" - the baloma language. Malinowski briefly refers to these songs but does not mention that they codify many aspects of Trobriand eschatology. The songs are still sung at specific occasions; however, they are now moribund. With these songs Trobriand eschatology will vanish.